STORAGE CHARACTERISTICS OF SPIKES AND GRAINS OF BREAD WHEAT CULTIVARS - & et al., Cheyed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to identify the storage characteristics of spikes of five bread wheat cultivars (Abu-Ghraib3, IPA-99, Boohooth-22, Al-Rashid and Al-Wafeer). These spikes were gathered and compacted in cubic box (25×25×25 cm) with different weight masses (0, 3, 6 and 9 kg container -1). A laboratory experiment was carried out in the Seed Technology Laboratory, Department of Field Crop Sciences, College of Agricultural Engineering Sciences-University of Baghdad. Results revealed significant differences among cultivars, masses levels and their interaction for all studied characters. Abu-Ghraib3 gave the highest mean of spikes number and less mean for the broken spikes and shuttered grains. While Al-Wafeer gave the highest mean of total grains weight resulted from spikes shuttering and grains space. However, Al-Rashid gave the highest mean of broken spikes, shuttered grains and replacement percentage in the container. Increasing the weight masses imposed on the gathered spikes in the container increased all studied characters. It can be concluded that the varieties were different in their spikes morphological characteristics as smaller spikes sizes the less losses resulted from spikes pressure.